Indonesia’s Diplomacy Jihad for Palestine at the United Nations Post-October 2023: A Critical Examination - Fathonah, Bikry; Paramitha, Salsabila Nayla; Pulungan, Fakhrul Haholongan; Muhammadin, Fajri Matahati (Universitas Islam Indonesia, 2026)
Historical ties between Indonesia and Palestine underpin Indonesia's steadfast commitment to supporting Palestine's right to independence. The Al-Aqsa Flood incident on October 7, 2023, followed by Israel’s massive invasion of Palestine, escalated the conflict in Palestine exponentially. This conflict has drawn the attention of the world, including Indonesia, to drastically intensify its diplomacy in supporting Palestine’s independence. Indonesia has undertaken a